Prevalence of Subclinical Keratoconus in Children with Astigmatism in Iraq - Layikh, Haider; Abbas, Farooq M.; Attar, Hasanain H.; Kadhum, Alyaa A. (Open Access Macedonian Journal of Medical Sciences, 2022)
Background: Keratoconus is a progressive ectatic corneal pathology that involves both eyes, its usually asymmetrical, its early diagnosis and treatment are vital for the prevention of ocular morbidity that usually happen if it’s not treated. Aim: To detect the prevalence of subclinical keratoconus and keratoconus suspect in children with the astigmatic error of ≥2 Diopters in Diwaniya city, Iraq. Methods: This is a cross-sectional, observational study, which investigates all the children aged six to eighteen years with an astigmatic error of ≥2 Diopters who attended the ophthalmology department for a routine eye examination during the period from January 2020 to June 2021. All children underwent full eye examination and corneal imaging study with a modern set which is a pentagram with Scheimpflug technology. Results: we had 488 children participated in our study, the Mean age of participants was 12.01 ± 1.24 (range 6–18) years, 255 children were males (52.2%) and 233 were female children (47.7%) and they were divided into 2 age groups: first one between 6 and 12 years 225 children ( 46.1%) the second one between 12 to 18 years include 263 children (53.8%). We found 21 children with subclinical keratoconus ( 4.3% ) and 24 children were keratoconus suspects ( 4.9% ). Conclusion: the prevalence of keratoconus whether subclinical or suspect among the children with astigmatism who enrolled in our study was relatively high, the use of modern imaging technique tests is vital in the diagnosis.